2023
DOI: 10.3390/molecules28062826
|View full text |Cite
|
Sign up to set email alerts
|

High-Branched Organosilicon Epoxy Resin with Low Viscosity, Excellent Toughness, Hydrophobicity, and Dielectric Property

Abstract: Rapidly developing technology places higher demands on materials, thus the simultaneous improvement of materials’ multiple properties is a hot research topic. In this work, a high-branched silicone epoxy resin (QSiE) was synthesized and applied to the curing system of bisphenol A epoxy resin (DGEBA) for modification investigations. When 6 wt% QSiE was added to the system, the viscosity dropped by 51.8%. The mechanical property testing results indicated that QSiE could significantly enhance the material’s tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Unique wetting phenomena, such as excellent hydrophobicity and hydrophilicity, can be exhibited by superwettable textured surfaces and have enabled a wide variety of applications in the fields of bionics, biosensing, surface performance improvement, and so on. Ultrafast laser processing has great potential in regulating the surface wettability of various materials and achieved significant applications. , The surface wettability of CFRP processed by a femtosecond laser with different laser pulse energies and scanning speeds is shown in Figure . The nontreated CFRP was hydrophobic, and its initial contact angle of water droplet was 105.6°, which was attributed to the good hydrophobicity of smooth epoxy resin on the surface of nontreated CFRP. Figure a shows the dependence of the droplet contact angle of the laser-processed CFRP on laser scanning speed. It revealed that the droplet contact angle of the laser-processed CFRP decreased with the decrease of laser scanning speed, and the rate of decrease was gradually slowing down.…”
Section: Resultsmentioning
confidence: 99%
“…Unique wetting phenomena, such as excellent hydrophobicity and hydrophilicity, can be exhibited by superwettable textured surfaces and have enabled a wide variety of applications in the fields of bionics, biosensing, surface performance improvement, and so on. Ultrafast laser processing has great potential in regulating the surface wettability of various materials and achieved significant applications. , The surface wettability of CFRP processed by a femtosecond laser with different laser pulse energies and scanning speeds is shown in Figure . The nontreated CFRP was hydrophobic, and its initial contact angle of water droplet was 105.6°, which was attributed to the good hydrophobicity of smooth epoxy resin on the surface of nontreated CFRP. Figure a shows the dependence of the droplet contact angle of the laser-processed CFRP on laser scanning speed. It revealed that the droplet contact angle of the laser-processed CFRP decreased with the decrease of laser scanning speed, and the rate of decrease was gradually slowing down.…”
Section: Resultsmentioning
confidence: 99%